2014
DOI: 10.1371/journal.pone.0102696
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Characterisation of Antimicrobial Properties of Semisynthetic Betulin Derivatives

Abstract: Betulin (lup-20(29)-ene-3β, 28-diol) is a naturally occurring triterpene, which is found in substantial amounts from the outer bark of birch trees. A library of 51 structurally diverse semisynthetic betulin derivatives was screened against five bacterial strains, Enterobacter aerogenes, Escherichia coli, Enterococcus faecalis, Pseudomonas aeruginosa, Staphylococcus aureus and a fungal strain Candida albicans, using broth microdilution assays. Primary antimicrobial screening at 50 µM concentration led to the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 54 publications
1
35
0
2
Order By: Relevance
“…However, another study confirmed the inhibitory activity of BA isolated from Forsythia suspensa VAHL towards the urease enzyme of H. pylori (Shin et al 2009). Despite these contradictions, some derivatives of BE were reported to exhibit antibacterial activity, which seems like a promise for future applications (Chue et al 2011;Haque et al 2014).…”
Section: Anti-tumoral Activity Of Be and Bamentioning
confidence: 99%
“…However, another study confirmed the inhibitory activity of BA isolated from Forsythia suspensa VAHL towards the urease enzyme of H. pylori (Shin et al 2009). Despite these contradictions, some derivatives of BE were reported to exhibit antibacterial activity, which seems like a promise for future applications (Chue et al 2011;Haque et al 2014).…”
Section: Anti-tumoral Activity Of Be and Bamentioning
confidence: 99%
“…The difference in the cognitive-enhancing activity of these two pentacyclic triterpenes, despite their structural similarity, might be related, in part, to their different distribution constants. 25,26) In this study, we show for the first time the memoryenhancing potential of betulin. Although more in vivo studies are needed to elucidate the mechanism of mammalian metabolites of betulin, we suggest that betulin has potential as a candidate as cognitive-enhancing therapeutic agent to attenuate the progression of AD.…”
Section: Resultsmentioning
confidence: 59%
“…Considering these results, we assume that dihydrobetulinic acid and compound 2 are able to trigger the programmed cell death, including apoptotic mechanisms and cell cycle arrest in the S phase. Previously, it was shown that triterpene acids, either in a pure state or as parts of plant extracts, exhibit moderate bacteriostatic activity, mainly against Gram-positive bacteria [17][18][19]. The minimum inhibitory concentrations (MICs) of ursolic and oleanolic acids against various Staphylococcus aureus strains, including the methicillin-resistant (MRSA) strain, were in the range from 8 to 64 μg/mL, while betulinic acid was less active against these strains [20].…”
Section: Chemistrymentioning
confidence: 99%